A pericyte chloride clamp mechanism governs capillary control of cerebral blood flow - Liuruimin Xiang; Ashwini Hariharan; Dominic Isaacs; Nick Weir; Thomas A. Longden (Proceedings of the National Academy of Sciences, 2026)
Thin-strand pericytes cover the deepest reaches of the brain’s capillary network, and their fine processes are intimately associated with adjacent endothelial cells (ECs). Recent work has revealed that thin-strand pericytes contribute to electrical signaling throughout the brain’s vasculature by generating hyperpolarizing signals that can be transmitted over long distances to relax remote ensheathing pericytes around proximal branches of the capillary bed and smooth muscle cells (SMCs) around arterioles, thereby eliciting blood flow increases. Resetting hyperpolarizing events in thin-strand pericytes must involve the engagement of ion channels that carry depolarizing currents, but the channels that mediate such conductances are unknown. Here, we reveal that thin-strand pericytes of the mouse cortex express functional TMEM16A calcium (Ca 2+ )-activated chloride (Cl − ) channels (CaCCs) encoded by the Ano1 gene, and we demonstrate that these are controlled by endoplasmic reticulum (ER) Ca 2+ release through ryanodine receptors (RyRs) and inositol-1,4,5-trisphosphate (IP 3 ) receptors (IP 3 Rs), and Ca 2+ entry via plasmalemmal L- and T-type voltage-dependent Ca 2+ channels (VDCCs). We show that the activity of thin-strand pericyte CaCCs plays a key role in tethering membrane potential close to E Cl to regulate upstream arteriole diameter in vivo. We term this mechanism the pericyte “Cl − clamp,” and we show that this functions to oppose hyperpolarizing electrical signaling and dilation under basal conditions and conversely opposes constriction under depolarizing conditions. We suggest that the operation of this VDCC-ER-CaCC unit is thus essential for optimal management of energy substrate delivery to local neurons.